The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.28991/cej-2023-09-04-012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plastic Waste on The Volumetric Characteristics and Resilient Modulus of Asphalt Concrete

Abstract: Recently, the use of plastic in many products has led to a huge amount of plastic waste, which is typically difficult to treat and expensive to recycle. This problem has been considered by many researchers and environmental organizations as requiring serious considerations about recycling and reusing plastic waste in different fields, such as asphalt mixtures. In this paper, aggregate passing a 4.75-mm sieve was replaced by 5, 7, 9, and 11% of plastic bottles used for drinking purposes. The dry method was adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
(23 reference statements)
1
0
0
Order By: Relevance
“…Similarly, as the pressing duration increased from 2 to 8 min, the water absorption decreased from 0.415 % to 0.275 %. The observed pattern of increasing and decreasing findings in this study, consistent with previous research reports referenced as [ 40 , 41 , 46 ], suggests a similar trend or phenomenon observed in those studies. The pressing duration, which refers to the duration of the highest-pressure application to minimize relaxation during paver tile production, influences water absorption, as evidenced by the decrease in water absorption with increasing pressing duration [ 28 , 31 ].…”
Section: Resultssupporting
confidence: 92%
“…Similarly, as the pressing duration increased from 2 to 8 min, the water absorption decreased from 0.415 % to 0.275 %. The observed pattern of increasing and decreasing findings in this study, consistent with previous research reports referenced as [ 40 , 41 , 46 ], suggests a similar trend or phenomenon observed in those studies. The pressing duration, which refers to the duration of the highest-pressure application to minimize relaxation during paver tile production, influences water absorption, as evidenced by the decrease in water absorption with increasing pressing duration [ 28 , 31 ].…”
Section: Resultssupporting
confidence: 92%